On mathematical model approach to competition dynamic of shipping companies in Surabaya - Windarto, ,-
Indonesia has a vast sea area and consists of many islands, so shipping companies are very beneficial for Indonesia's people. This study aims to estimate parameters and analyze mathematical models of shipping company competition between three shipping companies in Surabaya. This model is a differential equation and uses the Lotka- Volterra mathematical model. In this study, the estimation of model parameters is done using the genetic algorithm method based on the number of container production transported by shipping companies. The mathematical model is then analyzed by finding the equilibrium point and checking its stability by substituting the parameter value from the estimation results. The results of this mathematical simulation model show that the three companies exist in the future, and competition between the three companies still occurs